2011
DOI: 10.1016/j.aquaculture.2011.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of mussel (Aulacomya maoriana Iredale 1915) larval settlement by neuroactive compounds, amino acids and bacterial biofilms

Abstract: Please cite this article as: Alfaro, Andrea C., Young, Tim, Ganesan, Annapoorna Maitrayee, Regulatory effects of mussel (Aulacomya maoriana Iredale 1915) larval settlement by neuroactive compounds, amino acids and bacterial biofilms, Aquaculture (2011), doi: 10.1016/j.aquaculture.2011.08.038 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typeset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 84 publications
(104 reference statements)
1
21
0
Order By: Relevance
“…GABA was also acutely toxic for P. canaliculus, with an LC50 of 1.7 * 10 − 4 M and for A. maoriana , although LC50 values were not provided for this species. Based on its highly acute toxic effect, Alfaro et al (2011) inferred that GABA would be unlikely to be a natural settlement cue, and our results reinforce this hypothesis. LC50 value for epinephrine (4.3 * 10 − 4 M) was also fairly high, however mortality was enhanced only in the higher concentration tested.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…GABA was also acutely toxic for P. canaliculus, with an LC50 of 1.7 * 10 − 4 M and for A. maoriana , although LC50 values were not provided for this species. Based on its highly acute toxic effect, Alfaro et al (2011) inferred that GABA would be unlikely to be a natural settlement cue, and our results reinforce this hypothesis. LC50 value for epinephrine (4.3 * 10 − 4 M) was also fairly high, however mortality was enhanced only in the higher concentration tested.…”
Section: Discussionsupporting
confidence: 81%
“…The mechanism by which GABA is able to induce settlement and metamorphosis in bivalves remains elusive. Yu et al (2008) reviewed that GABA impairs ciliar activity in mollusk larvae; Alfaro et al (2011) proposed an indirect mechanism of action by means of secretion of other substances. On the other hand, the current study reports for the first time to our knowledge the toxic effect displayed by GABA on M. galloprovincialis larvae: GABA enhanced mortality at all the concentrations tested, suggesting that this chemical would not act as a natural settlement promoter in larvae, which was also suggested byAlfaro et al (2011) for A. maoriana.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether this effect was caused by a coupling of the metamorphic gene regulatory network to the induced pre-metamorphic behavior/process prior to the event, or whether acetylcholine is directly involved in the morphogenic signalling pathway during the event. While acetylcholine is a potent inducer of larval settlement in some bivalve species (Yu et al 2008;Alfaro et al 2011;Young et al 2011;Sánchez-Lazo et al 2012), no effect on attachment or metamorphosis has been observed in the five Haliotis spp. tested thus far (H. discus [Fukazawa et al 2001], H. discus hannai [Akashige et al 1981], H. diversilcolor supertexta [Yu et al 2010], H. gigantea [Fukazawa et al 2001], H. rufescens [Morse et al 1979]).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether this effect was caused by a coupling of the metamorphic gene regulatory network to the induced pre-metamorphic behavior/process prior to the event, or whether acetylcholine is directly involved in the 17 morphogenic signalling pathway during the event. While acetylcholine is a potent inducer of larval settlement in some bivalve species (Yu et al 2008;Alfaro et al 2011;Young et al 2011;Sánchez-Lazo et al 2012) Resembling the effects of GABA, KCl, acetylcholine and dopamine, glutamine also reduced swimming activity in H. iris larvae within the first two days of exposure. Although there was some indication of induced attachment at high concentrations (10 -4 mol L -1 ), high mortalities (ca.…”
Section: Discussionmentioning
confidence: 99%
“…Larval settlement and metamorphosis are thought to be typically activated by various exogenous chemicals and other environmental stimuli (Hadfield & Paul ). Several physical, biological and chemical cues have been identified as inducers of larval settlement and/or metamorphosis across molluscan species (Hadfield & Paul ; Alfaro, Young, & Ganesan ). Such cues include substrate morphology (Hadfield & Paul ; Alfaro & Jeffs ), vibration (Rittschof, Forward, Cannon, Welch, McClary, Holm, Clare, Conova, McKelvey, Bryan, & van Dover ), water motion (Alfaro ), sound (Lillis, Eggleston, & Bohnenstiehl ), microbial biofilms (Ganesan, Alfaro, Brooks, & Higgins ; Tung & Alfaro ; Ganesan, Alfaro, Higgins, & Brooks ; Ganesan, Alfaro, Higgins, Duxbury, & Brooks ), the presence/absence of conspecifics and/or prey species (Hadfield & Paul ), and a range of natural or artificial chemicals (Steinberg, De Nys, & Kjelleberg ; Alfaro, Copp, Appleton, Kelly, & Jeffs ; Young, Alfaro, & Robertson ; Alfaro, Young, & Bowden ; Young, Alfaro, Sánchez‐Lazo, & Robertson ).…”
Section: Introductionmentioning
confidence: 99%